Energy and exergy analysis of an aromatics plant. (September 2016) - Vilarinho, A.N.; Campos, J.B.L.M.; Pinho, C.
Abstract: Energy and exergy balances were evaluated for the units that constitute the Aromatics plant of a refinery in Portugal (FAR): pre-distillation (Un-0100), Arosolvan (Un-0200), Parex (Un-0300), Isomar (Un-0400) and production of solvents (Un-0500). The FAR had an overall energy yield of 0.81% and an exergetic efficiency of 65.9%. The equipment with higher energy losses, were the condensers, representing 25.9% of the energy losses, followed by air coolers, with 15.4% of the energy losses. The furnaces were in third place with 14.7% of the energy losses. Most of the energy lost in FAR was due to the cooling process. The irreversibilities observed in the condensers and air coolers were equivalent to 1.61% and 0.86% of the total plant irreversibility. Furnaces represent 14.7% of energy losses, but stand out above the irreversibilities analysis with 14.5% of the total. This equipment presents a high potential of energetic and exergetic performance improving, with natural positive impact on energetic and exergetic performance in the FAR. The unaccounted thermal losses represented 32.9% which is mainly justified by the unknown mass flow rate of the gaseous effluent burned in the flare.